CHONDROSARCOMA OF THE PROXIMAL HUMERUS IN A STATE PHILANTHROPIC HOSPITAL - Henrique Campoy Guedes, Victor; Filgueira Leite, Iracema; Carlos de Lacerda Leite, José; Suely Queiroz Silva Ribeiro, Kátia; Sobreira Camurça, Rayssa; Vasconcelos Vieira Siqueira, Viviane; Alexandra Naranjo Espinoza, Verónica; Luís Lopes Gomes de Siqueira, André (Health and Society, 2023)
Objective: To analyze the clinical and epidemiological profile of patients with chondrosarcoma of the proximal humerus treated at a Philanthropic Hospital over a period of 5 years. Methods: Documentary, exploratory, descriptive study, conducted by 04 medical records of patients admitted to the Orthopedic Oncology service, with a diagnosis of chondrosarcoma located in the proximal humerus in the period 2014 to 2018. The sex, age, staging, radiology, and surgery performed were investigated. The data obtained were analyzed by descriptive statistics with the aid of the RStudio software. The study was approved by the Research Ethics Committee. Results: All patients were female, and the age ranged from 37 to 50 years. The most frequent symptom was mild local pain, there was no evidence of loss of function at the time of diagnosis. Radiology showed an expansive, lobulated lesion with intermingled calcification. Histology, two cases of grade I chondrosarcoma, one case grade II and one grade III. Enneking I staging 50% and Enneking II in 2 cases. Surgery ranged from local curettage to en bloc resection. Recurrence was null at follow-up time. Conclusion: It is a rare disease with a small number of cases, but it initiates an analysis for further studies in its epidemiology and treatment.